Karya Tari Rang Babanjuang Interpretasi Proses Pembangunan Gaduang-Gaduang Terbuka - Awal, Ramadhan; Ilham, Kurniadi; Metro, Wardi; Emri (JURNAL ILMIAH NUSANTARA, 2025)
The Rang Babanjuang dance is inspired by a cultural phenomenon in the Dharmasraya region, specifically on the Dareh River, namely the activities of farmers in building gaduang-gaduang (a kind of structure) in rice fields and plantations. The construction of gaduang-gaduang embodies the values of togetherness, one of which is mutual cooperation. This dance expresses how farmers carry out their work cooperatively, embodying the values of togetherness. Rang Babanjuang is a contemporary group dance with an abstract style and cultural theme, utilizing dance movements and techniques. To interpret ideas in accordance with the concept being developed, this work uses the methods of Alma M. Hawkins, namely data collection and field observation, exploration, improvisation, formation, and evaluation. This work involves seven male dancers.